2016
DOI: 10.1186/s12943-016-0511-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BMP and of TGFβ receptors downregulates expression of XIAP and TAK1 leading to lung cancer cell death

Abstract: BackgroundBone morphogenetic proteins (BMP) are embryonic proteins that are part of the transforming growth factor (TGFβ) superfamily, which are aberrantly expressed in many carcinomas. Inhibition of BMP receptors with small molecule inhibitors decreases growth and induces death of lung cancer cells, which involves the downregulation of Id1 and Id3 by a Smad dependent mechanism. Developmentally, BMP and TGFβ signaling utilizes Smad-1/5 independent mechanisms to stabilize the expression of X-linked inhibitor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…NF-κB is part of the immune defense mechanism and a master regulator of inflammation (97). Increased NF-κB activity is sufficient to drive chronic inflammation (98) and may explain the TLR4 hyperresponsiveness we observed (99). Unexpectedly, FOP macrophages' hyperresponsiveness is likely mediated by 2 different pathways, whether they are monocytes (NF-κB) or differentiated antiinflammatory macrophages (p38).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 82%
“…NF-κB is part of the immune defense mechanism and a master regulator of inflammation (97). Increased NF-κB activity is sufficient to drive chronic inflammation (98) and may explain the TLR4 hyperresponsiveness we observed (99). Unexpectedly, FOP macrophages' hyperresponsiveness is likely mediated by 2 different pathways, whether they are monocytes (NF-κB) or differentiated antiinflammatory macrophages (p38).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 82%
“…A number of studies have examined the association of abnormal BMP signalling with cancer initiation and/or progression. Changes in BMP signaling via the Smad cascade has been associated with a number of tumour types [ 6 , 7 ]. Also, BMP-2, -4 and -7 have exhibited altered expression in many types of malignancies including breast, prostate, osteosarcoma, glioma, ovarian, pancreatic, lung, and other cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of BMPR2 decreases the expression of XIAP in lung cancer cell lines and increases cytosolic cytochrome c and Smac/DIABLO [22]. The BMP inhibitors JL5 and DMH2 decrease the expression of XIAP and cause more cell death than the BMP inhibitors DMH1 and LDN [7,8]. JL5 and DMH2 both demonstrate some inhibition of BMPR2 with in vitro phosphorylation kinase assays with an IC50 of approximately 8 mM [8].…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung carcinomas (NSCLC), the BMP-2 ligand is over-expressed 17-fold higher in comparison to normal lung tissue and benign lung tumors [4]. A number of studies have shown that BMP signaling has signi cant tumorigenic effects that involve the regulation of cell survival, migration, proliferation, stemness, and angiogenesis, and that high ligand expression correlates with a worse prognosis [3,[5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation